The Training Graduates Performance of BKKBN Family Planning Extension Workers - Rivendri Rivendri; Wirdatul Aini (Universitas Negeri Padang, 2021)
This research was motivated by the performance of graduates of the family planning counseling training at the West Sumatra BKKBN which was categorized as good. This is the implementation of activities that are carried out well even with the use of new methods applied. The objectives of this study are (1) to see the work ability of graduates from family planning extension training at BKKBN West Sumatra (2) to see the work motivation of graduates from training to family planning extension workers at BKKBN West Sumatra (3) to examine the work environment of graduates from training for family planning extension workers at BKKBN West Sumatra This research is a research with a quantitative approach and the type of this research is descriptive. The population in this study were 29 people, the sampling technique was stratified random sampling and taken as many as 75% or consisted of 22 people. Techniques in data collection using written statements (questionnaires) and data collection tools in the form of a list of statements. The data analysis technique uses the percentage formula. The results of this study indicate that: (1) the performance of graduates from training for family planning extension workers at BKKBN West Sumatra. Judging from the sub-variables, the work ability is categorized as good. (2) the performance of BKKBN family planning instructor training graduates in West Sumatra. Judging from the sub-variables of work motivation, it is categorized as good. (3) the performance of BKKBN family planning instructor training graduates in West Sumatra. Judging from the sub-variables the work environment is categorized as good. It is hoped that further researchers will be able to examine new variables so that they can complete the variables in their research.